2016
DOI: 10.1097/brs.0000000000001591
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition Predicts Infectious and Wound Complications Following Posterior Lumbar Spinal Fusion

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
105
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 27 publications
7
105
1
1
Order By: Relevance
“…The current study con rmed that perioperative hypoalbunemia was an important risk factors for wound complications following single-segment PLIF surgery [22][23][24][25][26][27]. Our study further con rmed that perioperative hypoalbuminemia are important risk factors for SWD and SSI.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The current study con rmed that perioperative hypoalbunemia was an important risk factors for wound complications following single-segment PLIF surgery [22][23][24][25][26][27]. Our study further con rmed that perioperative hypoalbuminemia are important risk factors for SWD and SSI.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, they retrospectively reviewed data prospectively collected by the American College of Surgeons National Surgical Quality Improvement Program to investigate the relationship between preoperative hypoalbuminemia and complications after 30 days of posterior lumbar fusion. They pointed out that malnutrition was an independent risk factor for infection and wound complications after posterior lumbar fusion, and it was also associated with increased length of stay and readmission [31].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Therefore, patients with preoperative hypoalbuminemia have a higher risk of complications related to the healing of the surgical wound. 1,3,15,20 This study, however, found no significant correlation between preoperative hypoalbuminemia and the rates of postoperative infection or of complications in the wound-healing process. Some authors affirm that albumin should not be used as a standalone criterion for the nutritional assessment of patients, and that it should be associated with other nutritional indicators, such as anthropometry and body composition.…”
Section: Discussionmentioning
confidence: 42%
“…Therefore, it can minimises protein loss, improve patient comfort and decrease insulin resistance (21). Good nutritional status could reduce the occurrence of complications such as wound infections and may help wound healing (22). Research examining shortening preoperative fasting and postoperative eating time of elderly patients with lumbar surgery is markedly lacking, despite studies indicating that it is safe and effective (1,18,23).…”
Section: Discussionmentioning
confidence: 99%